If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4+1-3m-3m=-2m-3m
We simplify the equation to the form, which is simple to understand
4+1-3m-3m=-2m-3m
We move all terms containing m to the left and all other terms to the right.
-3m-3m+2m+3m=-4-1
We simplify left and right side of the equation.
-1m=-5
We divide both sides of the equation by -1 to get m.
m=5
| 1.2(7.2-0.3x)=-4.1x | | 4x-3(-2x+5)=40 | | 2x^2+3x-24=0 | | x^2-24x+50=-8x+2 | | x+2x+(x-12)=180 | | -(8y+2)-(7y-5)=-1 | | 9-1/2(3n-6)=n+2 | | 20n+4=24n-40 | | 2b+4=9+3b | | 5(x-2)=10(2-x) | | 0=z^2-(1+2i)z-x+2i | | 1+6x+3=5x+2 | | 0.5x^2-6=x^2+4x | | 4x+8+3x+9=13 | | f=-9+16 | | 15-8*2+12= | | -7p-4=-2p-14 | | 2[4-2(3-x)]-1=4[2(x-3)+7]-25 | | 99-4b=-11b | | 1+1+7a+3=a-1+4a | | .75k-.75=7 | | -8+b=4 | | x*5=x+4 | | 5x+45-3x=15 | | x+(x+5)+x+(x+5)=86 | | 2.25-.25g=.50g | | 5x+45+3x=15 | | 23x^2+22x=0 | | s^2=18-3s | | X+x+5+x+x+5=86 | | 23x+22x=0 | | (8p+4)+(9p+9)= |